2015
DOI: 10.1038/srep09525
|View full text |Cite
|
Sign up to set email alerts
|

A large temperature fluctuation may trigger an epidemic erythromelalgia outbreak in China

Abstract: Although erythromelalgia (EM) has been documented in the literature for almost 150 years, it is still poorly understood. To overcome this limitation, we examined the spatial distribution of epidemic EM, and explored the association between temperature fluctuation and epidemic EM outbreaks in China. We searched all peer-reviewed literature on primary epidemic EM outbreaks in China. A two-stage model was used to characterize the relationship between temperature fluctuation and epidemic EM outbreaks. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Due to little attention to EM by the public, no mass media reported EM during this outbreak, which adds weight to the utility of Internet search data and how it reflects individual’s health concerns and issues 29 . However, epidemic EM have mainly occurred in students living in schools, which makes our results useful for extrapolating to a similar population rather than general population 14 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Due to little attention to EM by the public, no mass media reported EM during this outbreak, which adds weight to the utility of Internet search data and how it reflects individual’s health concerns and issues 29 . However, epidemic EM have mainly occurred in students living in schools, which makes our results useful for extrapolating to a similar population rather than general population 14 .…”
Section: Discussionmentioning
confidence: 89%
“…Most epidemic EM outbreaks in China have been reported between February and March, coinciding with a V-shaped temperature change: namely a sharp temperature decline followed by a rapid temperature rise within a few days. Previous studies have hypothesized that these large temperature fluctuations that occur in South China are associated with epidemic EM outbreaks 6 7 8 11 12 13 14 . Furthermore, Liu et al 14 recently found that one degree Celsius increment of daily temperature might trigger an average rise of 1.22 EM cases in epidemic EM outbreak.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are also examples of infectious disease prediction based on environmental factors such as weather [34][35][36][37]. Previous studies have confirmed that weather data comprises a factor that has a great influence on the occurrence of infectious diseases [38][39][40]. Liang et al showed that rainfall and humidity are risk factors for a hemorrhagic fever with a renal syndrome [41].…”
Section: Introductionmentioning
confidence: 99%
“…Tham and Giles rapported that erythromelalgia is associated with a neuropathy of small fibers and primary vasculopathies, characterized by an intermittent increase of blood flow, hypoxia, and possibly shunts, with increase in local cellular metabolism [5]. Due to the hypothesis of shunts, substances that alter the distribution of skin blood flow can improve the cutaneous oxygenation and induce symptoms relief [6]. Aspirin, which inhibits platelet aggregation can quickly relief the secondary symptoms of coagulopathy.…”
Section: Sirmentioning
confidence: 99%